Non-destructive honey adulteration fraud identification using hyperspectral imaging and deep learning - Muhammad Aqeel; Shahzad Hussain; Hammad Shahab; Khan Bahadar Khan; Kashif Munir (Food Control, 2026)

Structural and physiological adaptations conferring herbivory resistance in wild olive (Olea europaea L. subsp. cuspidata) - Faakeha Islam; Syed Mohsan Raza Shah; Farooq Ahmad; Mansoor Hameed; Sana Basharat; Sana Fatima; Ansar Mehmood; Zahida Parveen; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Khawaja Shafique Ahmad (Physiology and Molecular Biology of Plants, 2026)

An analysis of impact of soil co-pollution with lead and traditional/biodegradable microplastics on growth characteristics of maize (Zea mays L.) - Muhammad Kashif Irshad; Saba Saleem; Jamilur R. Ansari; Ali Noman; Muhammad Aqeel; Mohamed O. Alshahrani; Modhi O. Alotaibi; Muhammad Sohaib Irshad; Sang Soo Lee (Journal of Environmental Sciences, 2026)

Assessment of functional trait variation in arid-zone plant families to evaluate indicator species for rehabilitation of degraded landscapes - Eisha Kanwal; Farooq Ahmad; Ansa Asghar; Ummar Iqbal; Anum Javaid; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Saba Gul; Muhammad Irshad; Khawaja Shafique Ahmad (The Science of Nature, 2026)

Melatonin Buffers Microplastic-induced Oxidative Stress in Rice by Restoring Redox Balance, Antioxidants Reprogramming and Phytohormone Homeostasis - Ali Noman; Osman Sonmez; Noreen Khalid; Muhammad Kashif Irshad; Afrah E. Mohammed; Modhi O. Alotaibi; Muhammad Aqeel (Journal of Soil Science and Plant Nutrition, 2026)

Wave energy converters for mild and low sea states: Classification, design optimization, and performance assessment — A review - Aqeel Ahmed; Z. Nizamani; A.K. Muhammad; Akihiko Nakayama; Mohamed Mubarak Abdul Wahab (Ocean Engineering, 2026)

A freak-wave event-curation workflow for predicting mooring-line tensions and platform response of floating offshore wind turbines - A.K. Muhammad; Z. Nizamani; Aqeel Ahmed; Akihiko Nakayama; Mirza Munir Ahmed (Ocean Engineering, 2026)

Desert treasures: a comprehensive review of the diversity, phytochemistry, ethnobotany, and conservation of thar desert flora - Ummar Iqbal; Hafiza Zahra Naseem; Hadia Jabeen; Muhammad Faraz Gul; Saba Gul; Nargis Naz; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf (The Science of Nature, 2026)

Correction to: Structural and functional traits governing the adjustments, survival, and success of C₄ grasses in arid and semi-arid environments - Marwah Saif; Farooq Ahmad; Jazab Shafqat; Ummar Iqbal; Ansa Asghar; Anum Javaid; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Khawaja Shafique Ahmad (Plant and Soil, 2026)

Structural and functional traits governing the adjustments, survival, and success of C₄ grasses in arid and semi-arid environments - Marwah Saif; Farooq Ahmad; Jazab Shafqat; Ummar Iqbal; Ansa Asghar; Anum Javaid; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Khawaja Shafique Ahmad (Plant and Soil, 2026)

Integrated GC–MS phytochemical analysis and in vivo assessment of antiarthritic activity of Curcuma zedoaria extracts - Yusra Wasti; Syeda Aroosa Mohsin; Muhammad Tahir Aqeel; Sania Atta; Nadeem ul Hassan Khan; Syeda Ayesha Farhana; Humaira Fatima; Iffat Naz (Inflammopharmacology, 2026)

Climate-driven Modifications in Structural and Functional Traits of Couch Grass [Cynodon Dactylon (L.) Pers.] along Elevation Gradient - Sana Fatima; Farooq Ahmad; Zahida Parveen; Sana Basharat; Mansoor Hameed; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Syed Mohsan Raza Shah; Raza Shah; Muhammad Ashraf; Muhammad Kaleem; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Trait dynamics of endemic Festuca species reveal cold-resilience across elevation gradient - Khawaja Shafique Ahmad; Syed Mohsan Raza Shah; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Ummar Iqbal; Ansar Mehmood; Sana Fatima; Wisal Muhammad Khan; Muhammad Ashraf; Hazem M. Kalaji; Manzer H. Siddiqui (Acta Physiologiae Plantarum, 2026)

Multifunctional bio-composite hydrogels: PolyAMPs-tuned hydroxyapatite-PVA/gelatin systems development and characterization - Anum Ayub Awan; Waheed Miran; Muhammad Bilal Khan Niazi; Zakir Hussain; Aqeel Afzal; Usman Liaqat (Sustainable Chemistry and Pharmacy, 2026)

Root microstructural traits regulate ion homeostasis in bush morning glory (Ipomoea carnea Jacq.) for invasiveness success in saline environments - Syed Mohsan Raza Shah; Naila Hadayat; Jazab Shafqat; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Maham Zia; Zaheer Abbas; Zahida Parveen; Muhammad Ashraf; Ummar Iqbal; Ansa Asghar; et al. (The Science of Nature, 2026)

Synergistic effects of biochar and silicon dioxide nanoparticles abate cadmium uptake and oxidative stress in tomato: Achieving crop resilience and environmental sustainability - Muhammad Kashif Irshad; Muhammad Waseem; Saba Saleem; Jamilur R. Ansari; Sana Ashraf; Wasim Javed; Ali Noman; Muhammad Aqeel; Muhammad Rizwan; Afrah E. Mohammed; Modhi O. Alotaibi; Muhammad Rizwan; et al. (Plant Science, 2026)

Unveiling the charge transfer pathways in CuWO4/NiFe/SnWO4 coupled S-scheme heterojunction for photocatalytic dye degradation - Rimsha Aqeel; Tanveer Hussain Bokhari; Saqib Javaid; Amina Zafar; Muhammad Inayat Ullah; Muhammad Tariq Nadeem; Atia Khalid; Shafqat Karim; Ting Zhu; Amjad Nisar; Mashkoor Ahmad (Journal of Water Process Engineering, 2026)

Enhanced bacteria-fungi associations and soil microbial network stability underpin ecosystem multifunctionality across a 53-year desert restoration chronosequence - Qingqing Hou; Muhammad Aqeel; Longwei Dong; Jie Peng; Ying Sun; Fan Li; Dong Tang; Bodong Yuan; Xusheng Guo; Jinzhi Ran; Weigang Hu; Xinrong Li; et al. (Journal of Environmental Management, 2026)

Seed Priming with Osmolytes Ameliorates Salinity Tolerance in Maize (Zea mays L.) Through Embryonic Modifications - Paris Riaz; Ansa Asghar; Sana Fatima; Sana Basharat; Zahida Parveen; Mansoor Hameed; Farooq Ahmad; M. Sajid Aqeel Ahmad; Muhammad Ashraf; Faakeha Islam; Syed Mohsan Raza Shah; Qasim Ali (Journal of Plant Growth Regulation, 2026)

Halotolerant PGPRs attenuate salinity stress in maize through differential expression of stress-related genes and regulated Na+/K+ homeostasis - Tahira Yasmeen; Muhammad Saleem Arif; Aqeel Ahmad; Muhammad Usman; Mohsin Tariq; Waqas Haider; Afira Syrish (South African Journal of Botany, 2025)

Synergistic effects of selected ethnomedicinal plants with Metronidazole against resistant H. Pylori, and their urease inhibition mechanism - Sania Atta; Marya Nawaz Malik; Muhammad Tahir Aqeel; Iffat Naz; Nadeem Irshad; Sadaf Naz; Nadeem ul Hassan Khan; Faisal Rasheed; Humaira Fatima (South African Journal of Botany, 2025)

Ecological resilience of Gallon's curse (Cenchrus biflorus Roxb.) in hyperarid and hypersaline environments - Sana Basharat; Farooq Ahmad; Mansoor Hameed; Zahida Parveen; Muhammad Sajid Aqeel Ahmad; Muhammad Waseem; Ansa Asghar; Sana Fatima; Liu Pingwu; Mehwish Noor; Syed Mohsan Raza Shah; Muhammad Ashraf (Journal of Arid Environments, 2025)

Phenotypic Plasticity of Safflower Genotypes in Response to Contrasting Climatic Conditions - Obaid Afzal; Mukhtar Ahmed; Sahir Hameed Khattak; Muhammad Aqeel Aslam; Saida Komal; Maryam Murtaza; Farrukh Bashir; Aqeel Ahmad; Aliya Mirbaz; Haroon Ur Rasheed; Ghulam Muhammad Ali; Muhammad Usman; et al. (Plant Molecular Biology Reporter, 2025)

Assessing virgin and reclaimed carbon fibre electrodes in structural batteries - James D. Randall; Aqeel Muhammad; Emma G. Hogan; Timothy Harte; Žan Simon; Bhagya Dhamarsiri; Leif E. Asp; Luke C. Henderson (Chemical Engineering Journal, 2025)

Dynamics of lumpy skin disease with treatment and viral factor monitoring through fractional operator - Parvaiz Ahmad Naik; Aqeel Ahmad; Qazi Muhammad Farooq; Muhammad Farman; Abdul Ghaffar; Kottakkaran Sooppy Nisar; Aceng Sambas; Zhengxin Huang (Modeling Earth Systems and Environment, 2025)

Rhizosphere fungal diversity and plant-fungi interaction surpass bacteria in predicting soil multifunctionality during restoration in the Tengger desert - Abdul Manan; Qingqing Hou; Weigang Hu; Muhammad Aqeel; Ying Sun; Haiyang Gong; Jinlong Li; Longwei Dong; Fan Li; Yan Deng; Xinrong Li; Jianming Deng (Journal of Soils and Sediments, 2025)

Prevalence and integrated risk assessment of antibiotics from River Chenab Pakistan; human and ecotoxicological prospectives - Aqeel Mahmood; Hafiz Muhammad Irfan; Alamgeer; Zeeshan Javed; Adeel Mahmood (Science of The Total Environment, 2025)

Morphological and physiological responses to aridity in narrowly- and widely-distributed plant species in drylands - Junlan Xiong; Weigang Hu; Allan Degen; Jie Peng; Longwei Dong; Li Yan; Qingqing Hou; Shuran Yao; Ying Sun; Xiaoting Wang; Yahui Zhang; Yan Deng; et al. (Science China Life Sciences, 2025)

Association of microplastics with lead and cadmium in soil: Land-use and temporal trends - Noreen Khalid; Muhammad Aqeel; Shiou Yih Lee; Ujala Ejaz; Ali Noman; Muhammad Faisal Maqsood; Muhammad Kashif Irshad; Mohamed A. El-Sheikh (Journal of Environmental Chemical Engineering, 2025)

Correction to: Control and effect of climate change due to human activities by mathematical modeling approach under fractional operator - Aqeel Ahmad; Khurram Faiz; Muhammad Farman; Sadia Sattar; Aceng Sambas (Modeling Earth Systems and Environment, 2025)

Control and effect of climate change due to human activities by mathematical modeling approach under fractional operator - Aqeel Ahmad; Khurram Faiz; Muhammad Farman; Sadia Sattar; Aceng Sambas (Modeling Earth Systems and Environment, 2025)

Stage-dependent synergistic impacts of AM fungi and rhizobacteria on phytohormone mediation and field productivity in dryland maize - Muhammad Abrar; Ying Zhu; Wen-Shan Li; Muhammad Aqeel; Umair Ashraf; Muhammad Maqsood Ur Rehman; Jian-Ming Li; Xiao-Fang Gong; Wasim Khan; Wei Wang; You-Cai Xiong (Field Crops Research, 2025)

Adaptive response of rare mountain sedge (Carex Ecostata C.B. Clarke) to hyper-cold environments - Ansa Asghar; Amina Ameer; Farooq Ahmad; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Mingzhou Qin; Asima Asghar; Shahid Ali Khan; Hao Yang Li; Zhan Fei Zhang (Plant and Soil, 2025)

Structural and functional traits driving Chloris flagellifera proliferation in arid saline environments - Ummar Iqbal; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Khawaja Shafique Ahmad; Ansar Mehmood; Nargis Naz; Muhammad Akram (Acta Physiologiae Plantarum, 2025)

Globally analysis of production of lactic acid by Lactobacillus plantarum AC11S: kinetics using Mittag-Leffler kernel via mathematical modeling - Muhammad Farman; Aqeel Ahmad; Muhammad Faheem; Kottakkaran Sooppy Nisar; Muhammad Saeed Akram; Hijaz Ahmad (Modeling Earth Systems and Environment, 2025)

Investigation of lassa fever with relapse and saturated incidence rate: mathematical modeling and control - Aqeel Ahmad; Usama Atta; Muhammad Farman; Kottakkaran Sooppy Nisar; Hijaz Ahmad; Evren Hincal (Modeling Earth Systems and Environment, 2025)

Microplastic Contaminated Root Zone Supplementation With Ascorbic Acid Enhance Photosynthesis, Antioxidant Defense, ROS Scavenging, and Secondary Metabolites in Rice - Khairiah Mubarak Alwutayd; Muhammad Aqeel; Noreen Khalid; Saher Nawaz; Noreen Akhter; Muhammad Kashif Irshad; Uthman Bagith Algopishi; Suliman Mohammed Suliman Alghanem; Ali Noman (Journal of Soil Science and Plant Nutrition, 2025)

Lyapunov global stability analysis and effects of serial killing on community disorder with generalized Mittag–Leffler kernel properties - Kottakkaran Sooppy Nisar; Aqeel Ahmad; Muhammad Farman; Evren Hincal; Rabia Sarwar (Modeling Earth Systems and Environment, 2025)

Competitive and synergistic effects of biochar modified with phosphoric acid and manganese oxide on the removal of Cd and Congo red from wastewater - Jing Qian; Qingsong Cai; Tao Zheng; Jizi Wu; Fuwei Sun; Rui He; Muhammad Aqeel Kamran; Jing Zhan; Xianhuai Huang (Journal of Water Process Engineering, 2025)

Mechanistic insight into interactive effect of microplastics and arsenic on growth of rice (Oryza sativa L.) and soil health indicators - Muhammad Kashif Irshad; Muhammad Aqeel; Saba Saleem; Wasim Javed; Ali Noman; Min Woo Kang; Noreen Khalid; Sang Soo Lee (Science of The Total Environment, 2024)

Spatial distribution and impacts of microplastics on potato growth and yield in agroecosystems in Sialkot, Pakistan - Zonaira Qaiser; Noreen Khalid; Adeel Mahmood; Zarrin Fatima Rizvi; Shiou Yih Lee; Muhammad Aqeel (Journal of Hazardous Materials, 2024)

Interactive effects of melatonin and salicylic acid on Brassica napus under drought condition - Noman Rafique; Noshin Ilyas; Muhammad Aqeel; Naveed Iqbal Raja; Ghulam Shabbir; Muhammad Ajaib; R. Z. Sayyed; Sulaiman Ali Alharbi; Mohammad Javed Ansari (Plant and Soil, 2024)

Correction: Examining Adaptive Responses of Foeniculum vulgare to Elevated Sodium and Chloride Stress in the Root Zone - Noreen Akhter; Rimsha Nafees; Ali Noman; Muhammad Aqeel; Naila Hadayat; Noreen Khalid; Abida Kausar; Mohammed O. Alshaharni; Muhammad Muslim Shahnaz; Arsal Saleem; Maryam M. Alomran (Journal of Soil Science and Plant Nutrition, 2024)

Examining Adaptive Responses of Foeniculum vulgare to Elevated Sodium and Chloride Stress in the Root Zone - Noreen Akhter; Rimsha Nafees; Ali Noman; Muhammad Aqeel; Naila Hadayat; Noreen Khalid; Abida Kausar; Mohammed O. Alshaharni; Muhammad Muslim Shahnaz; Arsal Saleem; Maryam M. Alomran (Journal of Soil Science and Plant Nutrition, 2024)

Recent development towards the novel applications and future prospects for cellulose-metal organic framework hybrid materials: a review - Zeenat Qamar; Awais Ali Aslam; Farheen Fatima; Sadaf Ul Hassan; Muhammad Shahid Nazir; Zulfiqar Ali; Sameer Ahmed Awad; Aqeel Ahmad Khan (Environmental Science and Pollution Research, 2024)

Reorientation of energy policy and management: Integrated Energy Planning (IEP) framework implementation for Renewable and Thermal Energy Systems (RTES) - Humera Tubussum; Muhammad Aslam; Hezlina Mohd Hashim; Maran Marimuthu; K.H. Mahmoud; Abdullah Saad Alsubaie; Abdul Waheed Bhutto; Aqeel Ahmed Bazmi; Awais Bokhari; Abdul-Sattar Nizami (Process Safety and Environmental Protection, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Efficacy of Fe-Mg-bimetallic biochar in stabilization of multiple heavy metals-contaminated soil and attenuation of toxicity in spinach (Spinacia oleracea L.) - Muhammad Kashif Irshad; Jong Cheol Lee; Muhammad Aqeel; Wasim Javed; Ali Noman; Su Shiung Lam; Ali El Naggar; Nabeel Khan Niazi; Hun Ho Lee; Muhammad Ibrahim; Sang Soo Lee (Chemosphere, 2024)

Preparation, characterization and functional evaluation of soy protein isolate-peach gum conjugates prepared by wet heating Maillard reaction - Arif Hussain; Muhammad Hussain; Waqas Ashraf; Aiman Karim; Sahibzada Muhammad Aqeel; Adil Khan; Asif Hussain; Salman Khan; Zhang Lianfu (Food Research International, 2024)

Long-term raw crop residue but not burned residue incorporation improved soil multifunctionality in semi-arid agroecosystems - Aqeel Ahmad; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Awais Shakoor; Shahid Iqbal; Asam Riaz; Anjum Zahid; Stephen James Chapman (Soil and Tillage Research, 2024)

Characterization of two novel fusariviruses co-infecting a single isolate of phytopathogenic fungus Botrytis cinerea - Aqeel Ahmed; Haris Ahmed Khan; Atif Jamal; Nasar Virk; Muhammad Faraz Bhatti (Virus Genes, 2024)

Impact of cement waste on soil fertility and crop productivity: a serious concern for food security - Junaid Iqbal; Muhammad Jamal Khan; Muhammad Hafeez; Junaid Ali Siddiqui; Muhammad Fahad; Bahar Ali; Muhammad Imran; Aqeel Ahmad; Shah Fahad (Environmental Science and Pollution Research, 2024)

Insights into the alleviation of cadmium toxicity in rice by nano-zinc and Serendipita indica: Modulation of stress-responsive gene expression and antioxidant defense system activation - Muhammad Faheem Adil; Shafaque Sehar; Zhengxin Ma; Khajista Tahira; Syed Muhammad Hassan Askri; Mohamed A. El-Sheikh; Aqeel Ahmad; Fanrui Zhou; Ping Zhao; Imran Haider Shamsi (Environmental Pollution, 2024)

Unveiling the detrimental effects of polylactic acid microplastics on rice seedlings and soil health - Muhammad Kashif Irshad; Min Woo Kang; Muhammad Aqeel; Wasim Javed; Ali Noman; Noreen Khalid; Sang Soo Lee (Chemosphere, 2024)

Binary mixture of ionic liquid and span 80 for oil spill remediation: Synthesis and performance evaluation - Masooma Nazar; Aqeel Ahmad; Syed Muhammad Shakil Hussain; Muhammad Moniruzzaman (Marine Pollution Bulletin, 2024)

Supplementation of nano-biochar improved growth and physiological attributes in wheat seedlings exposed to salt stress through enhanced activity of hydrolysing and nitrogen metabolic enzymes and regulation of crucial metabolites - Waqas Yousaf; Anis Ali Shah; Muhammad Bilal Afzal; Zaib-un Nisa; Naila Ali; Muhammad Yasin Ashraf; Hosam O. Elansary; Aqeel Ahmad (South African Journal of Botany, 2024)

Differential capacity of phragmites ecotypes in remediation of inorganic contaminants in coastal ecosystems: Implications for climate change - Noreen Akhter; Muhammad Aqeel; Shazia; Muhammad Kashif Irshad; Muhammad Muslim Shehnaz; Sang Soo Lee; Ali Noman; Asad Syed; A. Bokhari; Ali H. Bahkali; Ling Shing Wong (Environmental Research, 2024)

Biochar and nano biochar: Enhancing salt resilience in plants and soil while mitigating greenhouse gas emissions: A comprehensive review - Haider Sultan; Yusheng Li; Waqas Ahmed; Mu yixue; Asad Shah; Mohammad Faizan; Aqeel Ahmad; Hafiz Muhammad Mazhar Abbas; Lixiao Nie; Mohammad Nauman Khan (Journal of Environmental Management, 2024)

Harnessing Melatonin Protective Efficacy in Capsicum Plants Against Nickel-Contaminated Soil - Maryam M. Alomran; Ali Noman; Noreen Khalid; Naila Hadayat; Fatmah M. Alqahtani; Fahad Mohammed Alzuaibr; Noreen Akhter; Mohamed Hashem; Talaat Habeeb; Omar Mahmoud Al-Zoubi; Muhammad Aqeel (Journal of Soil Science and Plant Nutrition, 2024)

Enhancing systematic tolerance in Bermuda grass (Cynodon dactylon L.) through amplified alkB gene expression and bacterial-driven hydrocarbon degradation - Sehrish Iqbal; Ume Ummara; Sibgha Noreen; Muhammad Salim Akhter; Farrukh Jaleel; Shazia Jabeen; Nargis Naz; Abdul Wahid; Modhi O. Alotaibi; Mudawi M. Nour; Rahmah N. Al-Qthanin; Muhammad Aqeel (Environmental Science and Pollution Research, 2024)

Interplay between edaphic and climatic factors unravels plant and microbial diversity along an altitudinal gradient - Muhammad Aqeel; Noreen Khalid; Ali Noman; Jinzhi Ran; Abdul Manan; Qingqing Hou; Longwei Dong; Ying Sun; Yan Deng; Sang Soo Lee; Weigang Hu; Jianming Deng (Environmental Research, 2024)

Aggregation, toxicity, and biodegradability study of an ionic liquid-based formulation for effective oil spill remediation - Masooma Nazar; Mansoor Ul Hassan Shah; Aqeel Ahmad; Masahiro Goto; Wan Zaireen Nisa Yahya; Muhammad Moniruzzaman (Chemosphere, 2023)

Elucidating the Mechanistic Role of Zinc-Lysine to Enhance Cd Tolerance in Diverse Wheat (Triticum aestivum L.) Cultivars Through Distinct Morpho-Physio-Biochemical Improvements Under Cd Stress - Muhammad Hussaan; Saghir Abbas; Qasim Ali; Muhammad Sohail Akram; Kashif Tanwir; Ahmad Raza; Sherjeel Hashmat; Muhammad Aqeel; Hassan Javed Chaudhary; Muhammad Tariq Javed (Journal of Soil Science and Plant Nutrition, 2023)

Exogenous Application of Silicon and Sulfate Improved Drought Tolerance in Sunflowers Through Modulation of Morpho-physiological and Antioxidant Defense Mechanisms - Muhammad Nisar; Muhammad Aqeel; Abdul Sattar; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Umair Rasheed; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Fahad Mohammed Alzuaibr; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2023)

Correction to: Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman Khokhar; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Preparation of Tamsulosin Hydrochloride-Loaded Mucoadhesive In Situ Gelling Polymeric Formulation for Nasal Delivery in Geriatrics - Sadia Jafar Rana; Saman Zafar; Aqeel Shahzad; Muhammad Basit; Jahanzeb Mudassir; Muhammad Akhlaq; Tahir Ali Chohan; Muhammad Sohail Arshad (AAPS PharmSciTech, 2023)

Using walnut shells as low-cost adsorbent materials in an anaerobic filter medium of a De-centralized wastewater treatment system (DEWATS) - Muhammad Zaheer; Muhammad Shaham Ali; Ning Huang; Muhammad Aqeel Ashraf (Chemosphere, 2023)

Sequential anodic oxidation and cathodic electro-Fenton in the Janus electrified membrane for reagent-free degradation of pollutants - Zhen Qiu; Chiheng Chu; Kun Wang; Jianjian Shen; Xiaoying Zhu; Muhammad Aqeel Kamran; Baoliang Chen (Water Research, 2023)

Foliar architecture differentially restrains metal sequestration capacity in wheat grains (Triticum aestivum L.) grown in hyper-chloride-contaminated soils - Muhammad Sajid Aqeel Ahmad; Mansoor Hameed; Muhammad Kaleem; Sana Fatima; Farooq Ahmad; Muhammad Farooq; Mehtab Maratib; Iqra Aziz (Environmental Science and Pollution Research, 2023)

Molecular regulation of antioxidants and secondary metabolites act in conjunction to defend plants against pathogenic infection - Muhammad Usman Akbar; Muhammad Aqeel; Muhammad Shahzad Shah; Ghulam Jeelani; Naeem Iqbal; Ammara Latif; Rehab O. Elnour; Mohamed Hashem; Omar Mahmoud Alzoubi; Talaat Habeeb; Muhammad Qasim; Ali Noman (South African Journal of Botany, 2023)

Microplastics in soil differentially interfere with nutritional aspects of chilli peppers - Khadiga Alharbi; Muhammad Aqeel; Noreen Khalid; Atia Nazir; Muhammad Kashif Irshad; Fahad Mohammed Alzuaibr; Haifa AbdulAziz Sakit AlHaithloul; Noreen Akhter; Omar Mahmoud Al-Zoubi; Muhammad Qasim; Khalid M.Al Syaad; Manal Abdullah AlShaqhaa; et al. (South African Journal of Botany, 2023)

Lipoic Acid Positively Regulates Tomato Growth and Yield by Improving Organic Osmolytes and Antioxidant Defense System Under Saline Conditions - Rohina Bashir; Hafiza Naila Ramzan; Saqib Mahmood; Muhammad Awais; Samina Hassan; Muhammad Aqeel; Haifa A. S. Alhaithloul; Tasahil S. Albishi; Sameer H. Qari; Ali Noman (Journal of Soil Science and Plant Nutrition, 2023)

Exogenous Application of Moringa Leaf Extract Confers Salinity Tolerance in Sunflower by Concerted Regulation of Antioxidants and Secondary Metabolites - Fozia Farhat; Nadra Ashaq; Ali Noman; Muhammad Aqeel; Shameem Raja; Rashda Naheed; Muhammad Faisal Maqsood; Ijaz Haider; Arneeb Tariq (Journal of Soil Science and Plant Nutrition, 2023)

Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman KhokharVoytas; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

The presence of mycoviral infection attenuates the growth and pathogenicity of the phytopathogenic fungus Botrytis cinerea collected from strawberry fields in Pakistan - Aqeel Ahmed; Haris Ahmed Khan; Atif Jamal; Danish Ilyas Baig; Tehsin Fatma; Nasar Virk; Muhammad Faraz Bhatti (European Journal of Plant Pathology, 2023)

Colloidal gold based immunochromatographic detection of Mycoplasmopsis synoviae infection and its prevalence in avian species of Karachi, Pakistan - Nida Rehman; Uroosa Ejaz; Amal Siraj; Shazma Liaquat; Muhammad Sohail; Taseer Ahmed Khan; Syed Faraz Moin; Aqeel Ahmad (Research in Veterinary Science, 2023)

Soil-Root Relationship in a Leaf Succulent Halophyte Suaeda vera from Differently Salt-Affected Habitats - Naila Asghar; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad (Water, Air, & Soil Pollution, 2023)

Phytoremediation potential modulated by structural and functional traits in a saline desert halophyte Fagonia indica Burm. f - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Syed Mohsan Raza Shah; Farooq Ahmad; Majid Anwar; Sana Basharat; Ansa Asghar; Muhammad Ashraf (Environmental Science and Pollution Research, 2023)

Modulation of structural and functional traits in facultative halophyte Salvadora oleoides Decne. For adaptability under hyper-arid and saline environments - Ummar Iqbal; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Nargis Naz; Muhammad Ashraf; Muhammad Kaleem (Journal of Arid Environments, 2023)

Enhanced expression of xylanase in Aspergillus niger enabling a two-step enzymatic pathway for extracting β-glucan from oat bran - Yangyang Li; Cen Li; Sahibzada Muhammad Aqeel; Yachan Wang; Quan Zhang; Jianing Ma; Jingwen Zhou; Jianghua Li; Guocheng Du; Song Liu (Bioresource Technology, 2023)

Silicon Supplement Improves Growth and Yield Under Salt Stress by Modulating Ionic Homeostasis and Some Physiological Indices in Hordeum vulgare L - Muhammad Salim Akhter; Sibgha Noreen; Seema Mahmood; Muhammad Aqeel; Zafar Ullah Zafar; Muhammad Rashid; Muhammad Naveed Arshad; Muhammad Owais; Javid Ahmad; Kausar Hussain Shah (Journal of Soil Science and Plant Nutrition, 2023)

Glutathione treatment suppresses the adverse effects of microplastics in rice - Fu Chen; Muhammad Aqeel; Noreen Khalid; Muhammad Kashif Irshad; Fozia Farhat; Atia Nazir; Jing Ma; Muhammad Saeed Akhtar; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Ali Noman (Chemosphere, 2023)

Salt ion mediated changes in biochemical and anatomical characteristics of Brassica napus can be countered with Moringa Leaf extract - Noreen Akhter; Aqsa Noreen; Saima Saifullah; Ali Noman; Muhammad Muslim Shahnaz; Puleng M. Letuma; Abida Kausar; Maham Siddique; Mohamed Hashem; Saad Alamri; Omar Mahmoud Al-zoubi; Muhammad Saleem; et al. (South African Journal of Botany, 2023)

Interactive effects of polystyrene microplastics and Pb on growth and phytochemicals in mung bean (Vigna radiata L.) - Fu Chen; Muhammad Aqeel; Noreen Khalid; Atia Nazir; Muhammad Kashif Irshad; Muhammad Usman Akbar; Fahad Mohammed Alzuaibr; Jing Ma; Ali Noman (Journal of Hazardous Materials, 2023)

Dramatic changes in anatomical traits of a C4 grass Chrysopogon serrulatus Trin. (Poaceae) over a 1000 m elevational gradient - Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Mahwish Munir; Muhammad Ashraf; Syed Mohsan Raza Shah; Sana Basharat; Iftikhar Ahmad; Sangam Khalil (Journal of Mountain Science, 2023)

Integrative Evaluation of the Ecological Hazards by Microplastics and Heavy Metals in Wetland Ecosystem - Shanza Zaka; Muhammad Aqeel; Adeel Mahmood; Ali Noman; Zarrin Fatima Rizvi; Wajiha Sarfraz; Aisha Nazir; Komal Arshad; Noreen Khalid (Bulletin of Environmental Contamination and Toxicology, 2023)

Plant-soil-microbe interactions in maintaining ecosystem stability and coordinated turnover under changing environmental conditions - Muhammad Aqeel; Jinzhi Ran; Weigang Hu; Muhammad Kashif Irshad; Longwei Dong; Muhammad Adnan Akram; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Lai Fatt Chuah; Jianming Deng (Chemosphere, 2023)

Impact of plastic mulching as a major source of microplastics in agroecosystems - Noreen Khalid; Muhammad Aqeel; Ali Noman; Zarrin Fatima Rizvi (Journal of Hazardous Materials, 2023)

Toxicity and tolerance of nickel in sunflower (Helianthus annuus L.) - Muhammad Sajid Aqeel Ahmad; Alia Riffat; Mumtaz Hussain; Mansoor Hameed; Ambreen Khadija Alvi (Environmental Science and Pollution Research, 2023)

An assessment of the efficacy of biochar and zero-valent iron nanoparticles in reducing lead toxicity in wheat (Triticum aestivum L.). - Muhammad Nauman Mahamood; Sihang Zhu; Ali Noman; Abid Mahmood; Sana Ashraf; Muhammad Aqeel; Muhammad Ibrahim; Sobia Ashraf; Rock Keey Liew; Su Shiung Lam; Muhammad Kashif Irshad (Environmental Pollution, 2023)

Ecological health risk assessment of microplastics and heavy metals in sediments, water, hydrophytes (Alternanthera philoxeroides, Typha latifolia, and Ipomoea carnea), and fish (Labeo rohita) in Marala wetlands in Sialkot, Pakistan - Komal Arshad; Muhammad Aqeel; Ali Noman; Atia Nazir; Adeel Mahmood; Zarrin Fatima Rizvi; Wajiha Sarfraz; Sajjad Hyder; Shanza Zaka; Noreen Khalid (Environmental Science and Pollution Research, 2023)

Nerium oleander could be used for sustainable management of traffic-borne elemental-enriched roadside soils - Noreen Khalid; Ali Noman; Atia Nazir; Aasma Tufail; Naila Hadayat; Fahad Mohammed Alzuaibr; Sobia Ikram; Noreen Akhter; Mumtaz Hussain; Muhammad Aqeel (Environmental Science and Pollution Research, 2023)

Invasive success of Ipomoea carnea Jacq. through plasticity in physio-anatomical and phytochemical traits across diversified habitats - Syed Mohsan Raza Shah; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Muhammad Ashfaq Wahid (Biological Invasions, 2023)

Comparative Assessment of Remediation Potential of Xanthium strumarium Ecotypes in NaCl-Affected Root Zone - Noreen Akhter; Muhammad Aqeel; Muhammad Faisal Maqsood; Saher Nawaz; Muhammad Muslim Shahnaz; Noreen Khalid; Mohammed A. Basahi; Omar Mahmoud Al-Zoubi; Talaat Habeeb; Romina Alina Marc; Muhammad Kashif Irshad; Ali Noman (Water, Air, & Soil Pollution, 2022)

Elucidating the mechanisms determining the availability of phosphate by application of biochars from different parent materials - Muhammad Aqeel Kamran; Sadia Bibi; Baoliang Chen; Jun Jiang; Ren-Kou Xu (Environmental Geochemistry and Health, 2022)

Coupling biochar with microbial inoculants improves maize growth and nutrients acquisition under phosphorous-limited soil - Hafiz Muhammad Rashad Javeed; Rimsha Naeem; Mazhar Ali; Rafi Qamar; Muhammad Aqeel Sarwar; Fahim Nawaz; Atique-ur-Rehman; Muhammad Shehzad; Amjad Farooq; Haseeb-ur-Rehman; Samina Khalid; Khuram Mubeen; et al. (Acta Physiologiae Plantarum, 2022)

Continental‐scale niche differentiation of dominant topsoil archaea in drylands - Weigang Hu; Qingqing Hou; Manuel Delgado‐Baquerizo; James C. Stegen; Qiajun Du; Longwei Dong; Mingfei Ji; Yuan Sun; Shuran Yao; Haiyang Gong; Junlan Xiong; Rui Xia; et al. (Environmental Microbiology, 2022)
Archaea represent a diverse group of microorganisms often associated with extreme environments. However, an integrated understanding of biogeographical patterns of the specialist Haloarchaea and the potential generalist ammonia‐oxidizing archaea (AOA) across large‐scale environmental gradients remains limited. We hypothesize that niche differentiation determines their distinct distributions along environmental gradients. To test the hypothesis, we use a continental‐scale research network including 173 dryland sites across northern China. Our results demonstrate that Haloarchaea and AOA dominate topsoil archaeal communities. As hypothesized, Haloarchaea and AOA show strong niche differentiation associated with two ecosystem types mainly found in China's drylands (i.e. deserts vs. grasslands), and they differ in the degree of habitat specialization. The relative abundance and richness of Haloarchaea are higher in deserts due to specialization to relatively high soil salinity and extreme climates, while those of AOA are greater in grassland soils. Our results further indicate a divergence in ecological processes underlying the segregated distributions of Haloarchaea and AOA. Haloarchaea are governed primarily by environmental‐based processes while the more generalist AOA are assembled mostly via spatial‐based processes. Our findings add to existing knowledge of large‐scale biogeography of topsoil archaea, advancing our predictive understanding on changes in topsoil archaeal communities in a drier world.

Mediation of Growth and Metabolism of Pisum sativum in Salt Stress Potentially Be Credited to Thiamine - Rashda Naheed; Maryeum Zahid; Muhammad Aqeel; Muhammad Faisal Maqsood; Hina Kanwal; Noreen Khalid; Mohamed Hashem; Saad Alamri; Ali Noman (Journal of Soil Science and Plant Nutrition, 2022)

Contribution of structural and functional adaptations of hyper-accumulator Suaeda vera Forssk. ex J.F. Gmel. for adaptability across salinity gradients in hot desert - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Ashraf; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Syed Mohsan Raza Shah; Faakeha Islam; Iftikhar Ahmad; Farial Ejaz; Mehwish Naseer (Environmental Science and Pollution Research, 2022)

Unraveling the survival potential of a desert halophyte Salvadora oleoides Decne. across heterogenic environments - Ummar Iqbal; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf (Trees, 2022)

Survival strategies in two high altitude Sorghum species from western Himalayas - Khwaja Shafique Ahmad; Anum Javaid; Mansoor Hameed; Sana Fatima; Farooq Ahmad; Muhammad Ashraf; Syed Mohsan Raza Shah; Muhammad Sajid Aqeel Ahmad; Iftikhar Ahmad (Acta Physiologiae Plantarum, 2022)

Anatomical and physiological features modulate ion homeostasis and osmoregulation in aquatic halophyte Fimbristylis complanata (Retz.) link - Muhammad Kaleem; Mansoor Hameed; Farooq Ahmad; Muhammad Ashraf; Muhammad Sajid Aqeel Ahmad (Acta Physiologiae Plantarum, 2022)

Structural, Biochemical, and Physiological Adjustments for Toxicity Management, Accumulation, and Remediation of Cadmium in Wetland Ecosystems by Typha domingensis Pers - Noreen Akhter; Omey Habiba; Mehwish Hina; Muhammad Muslim Shahnaz; Fahad Mohammed Alzuaibr; Saad Alamri; Mohamed Hashem; Noreen Khalid; Muhammad Aqeel; Ali Noman (Water, Air, & Soil Pollution, 2022)

Modulation in Plant Micro-structures Through Soil Physicochemical Properties Determines Survival of Salsola imbricata Forssk. in Hypersaline Environments - Nargis Naz; Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Hina Shahid; Ummar Iqbal; Muhammad Kaleem; Syed Mohsan Raza Shah; Iftikhar Ahmad (Journal of Soil Science and Plant Nutrition, 2022)

Impact of COVID-19 on environmental ecosystem - Muhammad Aqeel Ashraf; Muhammad Faheem; Muhammad Azher Hassan (Environmental Science and Pollution Research, 2022)

Structural and Functional Determinants of Physiological Pliability in Kyllinga brevifolia Rottb. for Survival in Hyper-Saline Saltmarshes - Sahar Mumtaz; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Iftikhar Ahmad; Muhammad Ashraf; Muhammad Hamzah Saleem (Water, Air, & Soil Pollution, 2021)

Paclobutrazol Improves Sesame Yield by Increasing Dry Matter Accumulation and Reducing Seed Shattering Under Rainfed Conditions - Muhammad Zeeshan Mehmood; Ghulam Qadir; Obaid Afzal; Atta Mohi Ud Din; Muhammad Ali Raza; Imran Khan; Muhammad Jawad Hassan; Samrah Afzal Awan; Shakeel Ahmad; Muhammad Ansar; Muhammad Aqeel Aslam; Mukhtar Ahmed (International Journal of Plant Production, 2021)
Several biotic and abiotic stresses significantly decrease the biomass accumulation and seed yield of sesame crops under rainfed areas. However, plant growth regulators (such as Paclobutrazol) can improve the total dry matter and seed production of the sesame crop. The effects of the paclobutrazol application on dry matter accumulation and seed yield had not been studied before in sesame under rainfed conditions. Therefore, a two-year field study during 2018 and 2019 was conducted with key objectives to assess the impacts of paclobutrazol on leaf greenness, leaf area, total dry matter production and partitioning, seed shattering, and seed yield of sesame. Two sesame cultivars (TS-5 and TS-3) were treated with four paclobutrazol concentrations (P0 = Control, P1 = 100 mg L −1 , P2 = 200 mg L −1 , P3 = 300 mg L −1 ). The experiment was executed in RCBD-factorial design with three replications. Compared with P0, treatment P3 improved the leaf greenness of sesame by 17%, 38%, and 60% at 45, 85, and 125 days after sowing, respectively. However, P3 treatment decreased the leaf area of sesame by 14% and 20% at 45 and 85 days after sowing than P0, respectively. Compared with P0, treatment P3 increased the leaf area by 46% at 125 days after sowing. On average, treatment P3 also improved the total biomass production by 21% and partitioning in roots, stems, leaves, capsules, and seeds by 23%, 19%, 23%, 22%, and 40%, respectively, in the whole growing seasons as compared to P0. Moreover, under P3 treatment, sesame attained the highest seed yield and lowest seed shattering by 27% and 30%, respectively, compared to P0. This study indicated that by applying the paclobutrazol concentration at the rate of 300 mg L −1 in sesame, the leaf greenness, leaf areas, biomass accumulation, partitioning, seed yield, and shatter resistance could be improved. Thus, the optimum paclobutrazol level could enhance the dry matter accumulation and seed production capacity of sesame by decreasing shattering losses under rainfed conditions.

Wind speed pattern data and wind energy potential in Pakistan: current status, challenging platforms and innovative prospects - Hammad Saulat; Muhammad Masood Khan; Muhammad Aslam; Muhammad Chawla; Sikander Rafiq; Faisal Zafar; Muhammad Mahmood Khan; Awais Bokhari; Farrukh Jamil; Abdul Waheed Bhutto; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2021)

Correction to: Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Micro-morphological response of some native dicotyledonous species to particulate pollutants emitted from stone crushing activities - Iftikhar Ahmad; Lubaba Shamsi; Mansoor Hameed; Sana Fatima; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Anum Javaid; Muhammad Asim Sultan (Environmental Science and Pollution Research, 2021)

Can sulphur improve the nutrient uptake, partitioning, and seed yield of sesame? - Muhammad Zeeshan Mehmood; Obaid Afzal; Mukhtar Ahmed; Ghulam Qadir; Ahmed M.S. Kheir; Muhammad Aqeel Aslam; Atta Mohi Ud Din; Imran Khan; Muhammad Jawad Hassan; Tehseen Ahmad Meraj; Muhammad Ali Raza; Shakeel Ahmad (Arabian Journal of Geosciences, 2021)
Sulphur (S) is considered to improve the nutrient uptake of plants due to its synergistic relationship with other nutrients. This could ultimately enhance the seed yield of oilseed crops. However, there is limited quantitative information on nutrient uptake, distribution, and its associated impacts on seed yield of sesame under the S application. Thus, a two-year field study (2018 and 2019) was conducted to assess the impacts of different S treatments (S 0 = Control, S 20 = 20, S 40 = 40, and S 60 = 60 kg ha −1 ) on total dry matter production, nitrogen, phosphorus, potassium, S uptake and distribution at the mid-bloom stage and physiological maturity. Furthermore, treatment impacts were studied on the number of capsules per plant, number of seeds per capsule, thousand seed weight, and seed yield at physiological maturity in sesame. Compared to S 0 , over the years, treatment S 40 significantly increased the total uptake of nitrogen, phosphorus, potassium, and S (by 13, 22, 11% and 16%, respectively) at physiological maturity, while their distribution by 13, 36, 14, and 24% (in leaves), 12, 15, 11, and 15% (in stems), 15, 42, 18, and 10% (in capsules), and 14, 22, 9, and 15% (in seeds), respectively. Enhanced nutrient uptake and distribution in treatment S 40 improved the total biomass accumulation (by 28%) and distribution in leaves (by 34%), stems (by 27%), capsules (by 26%), and seeds (by 28%), at physiological maturity, as compared to S 0 . Treatment S 40 increased the number of capsules per plant (by 13%), number of seeds per capsule (by 11%), and thousand seed weight (by 6%), compared to S 0 . Furthermore, over the years, relative to control, sesame under S 40 had a higher seed yield by 28% and enhanced the net economic returns by 44%. Thus, our results suggest that optimum S level at the time of sowing improves the nutrient uptake and distribution during the plant lifecycle, which ultimately enhances total dry matter accumulation, seed yield, and net productivity of sesame.

Physiological homeostasis for ecological success of Typha (Typha domingensis Pers.) populations in saline soils - Noreen Akhter; Muhammad Aqeel; Muhammad Muslim Shahnaz; Ghalia S. H. Alnusairi; Suliman Mohammed Alghanem; Abida Kousar; Mohamed Hashem; Hina Kanwal; Saad Alamri; Aisha Ilyas; Omar Mahmoud Al-zoubi; Ali Noman (Physiology and Molecular Biology of Plants, 2021)

Nexus on climate change: agriculture and possible solution to cope future climate change stresses - Aqeel Shahzad; Sana Ullah; Afzal Ahmed Dar; Muhammad Fahad Sardar; Tariq Mehmood; Muhammad Aammar Tufail; Awais Shakoor; Muhammad Haris (Environmental Science and Pollution Research, 2021)

Rising Metals Concentration in the Environment: A Response to Effluents of Leather Industries in Sialkot - Noreen Khalid; Zarrin Fatima Rizvi; Nousheen Yousaf; Shujaul Mulk Khan; Ali Noman; Muhammad Aqeel; Komal Latif; Asmara Rafique (Bulletin of Environmental Contamination and Toxicology, 2021)

Survival Strategies in Khavi Grass [Cymbopogon jwarancusa (Jones) Schult.] Colonizing Hot Hypersaline and Arid Environments - Sana Fatima; Mansoor Hameed; Nargis Naz; Syed Mohsan Raza Shah; Mehwish Naseer; Muhammad Sajid Aqeel Ahmad; Muheammad Ashraf; Farooq Ahmad; Sangam Khalil; Iftikhar Ahmad (Water, Air, & Soil Pollution, 2021)

Environmental toxicology and biogeochemistry of ecosystems - Muhammad Aqeel Ashraf; Muhammad Faheem (Environmental Science and Pollution Research, 2020)

Bacterial-mediated synthesis of silver nanoparticles and their significant effect against pathogens - Saira Saeed; Atia Iqbal; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2020)

Enhancing phosphorus availability in two variable charge soils by the amendments of crop straw biochars - Muhammad Aqeel Kamran; Jackson Nkoh Nkoh; Ren-Kou Xu; Jun Jiang (Arabian Journal of Geosciences, 2020)

A forecasting model approach of sustainable electricity management by developing adaptive neuro-fuzzy inference system - Aamir Nawaz Khan; Muhammad Asif Nadeem; Muhammad Shahid Hussain; Muhammad Aslam; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2020)

Application of GIS/RS for monitoring of the ecological environment in a coastal zone - Rui Xie; Haihong Xiao; Muhammad Aqeel Ashraf (Arabian Journal of Geosciences, 2020)

Adaptations in Imperata cylindrica (L.) Raeusch. and Cenchrus ciliaris L. for altitude tolerance - Khawaja Shafique Ahmad; Ambreen Wazarat; Ansar Mehmood; Muhammad Sajid Aqeel Ahmad; Majid Mahmood Tahir; Fahim Nawaz; Haroon Ahmed; Mohsin Zafar; Aneela Ulfat (Biologia, 2020)

Land-use change in plateau lake basin and its impact on urban ecological security - Zijiang Yang; Xiong He; Muhammad Aqeel Ashraf (Arabian Journal of Geosciences, 2020)

The application of the intelligent algorithm in the prevention and early warning of mountain mass landslide disaster - Yuan Yan; Muhammad Aqeel Ashraf (Arabian Journal of Geosciences, 2020)

Access to clean technologies, energy, finance, and food: environmental sustainability agenda and its implications on Sub-Saharan African countries - Sanil S. Hishan; Sasmoko; Aqeel Khan; Jamilah Ahmad; Zainudin Bin Hassan; Khalid Zaman; Muhammad Imran Qureshi (Environmental Science and Pollution Research, 2019)

Socio-economic and environmental factors influenced the United Nations healthcare sustainable agenda: evidence from a panel of selected Asian and African countries - Hummera Saleem; Wen Jiandong; Abdullah Mohammed Aldakhil; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman; Aqeel Khan; Zainudin Bin Hassan; Mohd Rustam Mohd Rameli (Environmental Science and Pollution Research, 2019)

Sustaining life on earth system through clean air, pure water, and fertile soil - Muhammad Aqeel Ashraf; Marlia Mohd Hanafiah (Environmental Science and Pollution Research, 2019)

Foliar- and soil-applied salicylic acid and bagasse compost addition to soil reduced deleterious effects of salinity on wheat - Muhammad Imran Khan; Muhammad Aqeel Shoukat; Sardar Alam Cheema; Shafaqat Ali; Muhammad Azam; Muhammad Rizwan; Rashad Qadri; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2019)

Effects of road proximity on heavy metal concentrations in soils and common roadside plants in Southern California - Noreen Khalid; Mumtaz Hussain; Hillary S. Young; Benjamin Boyce; Muhammad Aqeel; Ali Noman (Environmental Science and Pollution Research, 2018)

Identification of phytotoxins in different plant parts of Brassica napus and their influence on mung bean - Azhar Mehmood; Muhammad Naeem; Farhan Khalid; Yousaf Saeed; Tasawer Abbas; Khawar Jabran; Muhammad Aqeel Sarwar; Asif Tanveer; Muhammad Mansoor Javaid (Environmental Science and Pollution Research, 2018)

Amelioration of soil acidity, Olsen-P, and phosphatase activity by manure- and peat-derived biochars in different acidic soils - Muhammad Aqeel Kamran; Jun Jiang; Jiu-yu Li; Ren-yong Shi; Khalid Mehmood; M. Abdulaha-Al Baquy; Ren-kou Xu (Arabian Journal of Geosciences, 2018)

Sugar beet extract acts as a natural bio-stimulant for physio-biochemical attributes in water stressed wheat (Triticum aestivum L.) - Ali Noman; Qasim Ali; Jazia Naseem; M. Tariq Javed; Hina Kanwal; Waqar Islam; Muhammad Aqeel; Noreen Khalid; Sara Zafar; Muhammad Tayyeb; Naeem Iqbal; Mahmooda Buriro; et al. (Acta Physiologiae Plantarum, 2018)

Incorporation of corn straw biochar inhibited the re-acidification of four acidic soils derived from different parent materials - Ren-yong Shi; Jiu-yu Li; Jun Jiang; Muhammad Aqeel Kamran; Ren-kou Xu; Wei Qian (Environmental Science and Pollution Research, 2018)

Higher cation exchange capacity determined lower critical soil pH and higher Al concentration for soybean - M. Abdulaha-Al Baquy; Jiu-yu Li; Ren-yong Shi; Muhammad Aqeel Kamran; Ren-kou Xu (Environmental Science and Pollution Research, 2018)

Association of textile industry effluent with mutagenicity and its toxic health implications upon acute and sub-chronic exposure - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Mohammad Saleem; Ghulam Mustafa; Moneeb Ashraf; Ammara Saleem; Bushra Akhtar (Environmental Monitoring and Assessment, 2018)

Beating cold by being tough: impact of elevation on leaf characteristics in Phleum himalaicum Mez. endemic to Himalaya - Khawaja Shafique Ahmad; Mansoor Hameed; Abdul Hamid; Fahim Nawaz; Bushra Hafeez Kiani; Muhammad Sajid Aqeel Ahmad; Jiabin Deng; Farooq Ahmad; Imtiaz Hussain; Sana Fatima (Acta Physiologiae Plantarum, 2018)

Basic leucine zipper domain transcription factors: the vanguards in plant immunity - Ali Noman; Zhiqin Liu; Muhammad Aqeel; Madiha Zainab; Muhammad Ifnan Khan; Ansar Hussain; Muhammad Furqan Ashraf; Xia Li; Yahong Weng; Shuilin He (Biotechnology Letters, 2017)

Recent advances in assessment on clear water, soil and air - Muhammad Aqeel Ashraf; Marlia Mohd Hanfiah (Environmental Science and Pollution Research, 2017)

The fate and transport of arsenic species in the aquatic ecosystem: a case study on Bestari Jaya, Peninsular Malaysia - Suzanne Christine Aboudi Mana; Ng Tham Fatt; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2017)

Chemical speciation and bioavailability of rare earth elements (REEs) in the ecosystem: a review - Aysha Masood Khan; Nor Kartini Abu Bakar; Ahmad Farid Abu Bakar; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2017)

Quality of tube well water intended for irrigation and human consumption with special emphasis on arsenic contamination at the area of Punjab, Pakistan - Atta Rasool; Tangfu Xiao; Abida Farooqi; Muhammad Shafeeque; Yizhang Liu; Muhammad Aqeel Kamran; Ioannis A. Katsoyiannis; Syed Ali Musstjab Akber Shah Eqani (Environmental Geochemistry and Health, 2017)

Retraction Note to: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2017)

Retraction Note to: Release, deposition and elimination of radiocesium (137Cs) in the terrestrial environment - Muhammad Aqeel Ashraf; Ayesha Masood Khan; Mushtaq Ahmad; Shatirah Akib; Khaled S. Balkhair; Nor Kartini Abu Bakar (Environmental Geochemistry and Health, 2017)

miRNAs: Major modulators for crop growth and development under abiotic stresses - Ali Noman; Shah Fahad; Muhammad Aqeel; Usman Ali; Amanullah; Sumera Anwar; Shahbaz Khan Baloch; Madiha Zainab (Biotechnology Letters, 2017)

miRNA-based heavy metal homeostasis and plant growth - Ali Noman; Muhammad Aqeel (Environmental Science and Pollution Research, 2017)

Occurrence and methods to remove arsenic and fluoride contamination in water - Sadia Bibi; Muhammad Aqeel Kamran; Jawairia Sultana; Abida Farooqi (Environmental Chemistry Letters, 2017)

Persistent organic pollutants (POPs): a global issue, a global challenge - Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2017)

Oxidative stress responses in Wistar rats on subacute exposure to pharmaceutical wastewater - Ali Sharif; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmed Anjum; Muhammad Furqan Akhtar; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

Dietary mycotoxins binders: a strategy to reduce aflatoxin m1 residues and improve milk quality of lactating Beetal goats - Haq Aman Ullah; Aneela Zameer Durrani; Muhammad Ijaz; Aqeel Javeed; Umer Sadique; Zahoor Ul Hassan; Altaf Ur Rahman; Muqader Shah; Irfan Khattak (Journal of Consumer Protection and Food Safety, 2016)

RETRACTED ARTICLE: Floristic and ethnoecological diversity in various habitats of a semi-arid area in the Chakwal district (Pakistan), with special emphasis on medicinal plants - Mehwish Jamil Noor; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Ismail Yusoff; Yatimah Alias; Muhammad Aqeel Ashraf (Plant Ecology, 2016)

Toxicity Appraisal of Untreated Dyeing Industry Wastewater Based on Chemical Characterization and Short Term Bioassays - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Ammara Saleem; Bushra Akhtar; Abdul Muqeet Khan; Imran Altaf (Bulletin of Environmental Contamination and Toxicology, 2016)

Pharmaceutical wastewater being composite mixture of environmental pollutants may be associated with mutagenicity and genotoxicity - Ali Sharif; Muhammad Ashraf; Aftab Ahmed Anjum; Aqeel Javeed; Imran Altaf; Muhammad Furqan Akhtar; Mateen Abbas; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

A review of the pollen analysis of South Asian honey to identify the bee floras of the region - Mehwish Jamil Noor; Mushtaq Ahmad; Muhammad Aqeel Ashraf; Muhammad Zafar; Shazia Sultana (Palynology, 2016)

Differential effects of cadmium and chromium on growth, photosynthetic activity, and metal uptake of Linum usitatissimum in association with Glomus intraradices - Amna; Naeem Ali; Sajid Masood; Tehmeena Mukhtar; Muhammad Aqeel Kamran; Mazhar Rafique; M. Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Monitoring and Assessment, 2015)

Effect of plant growth-promoting rhizobacteria inoculation on cadmium (Cd) uptake by Eruca sativa - Muhammad Aqeel Kamran; Jabir Hussain Syed; Syed Ali Musstjab Akber Shah Eqani; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2015)

RETRACTED ARTICLE: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2015)

RETRACTED ARTICLE: Release, deposition and elimination of radiocesium (137Cs) in the terrestrial environment - Muhammad Aqeel Ashraf; Ayesha Masood Khan; Mushtaq Ahmad; Shatirah Akib; Khaled S. Balkhair; Nor Kartini Abu Bakar (Environmental Geochemistry and Health, 2014)

Cesium-137: Radio-Chemistry, Fate, and Transport, Remediation, and Future Concerns - Muhammad Aqeel Ashraf; Shatirah Akib; Mohd. Jamil Maah; Ismail Yusoff; Khaled S. Balkhair (Critical Reviews in Environmental Science and Technology, 2014)

A review of the stabilization of tropical lowland peats - Mohamad Tarmizi Mohamad Zulkifley; Tham Fatt Ng; John Kuna Raj; Roslan Hashim; Ahmad Farid Abu Bakar; S. Paramanthan; Muhammad Aqeel Ashraf (Bulletin of Engineering Geology and the Environment, 2014)

The potential of the flora from different regions of Pakistan in phytoremediation: a review - Muhammad Aqeel Kamran; Amna; Rabia Mufti; Nadia Mubariz; Jabir Hussain Syed; Asghari Bano; Muhammad Tariq Javed; Muhammad Farooq Hussain Munis; Zhiyuan Tan; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2014)

Hydrogen sulfide ameliorates lead-induced morphological, photosynthetic, oxidative damages and biochemical changes in cotton - Saima Aslam Bharwana; Shafaqat Ali; Muhammad Ahsan Farooq; Basharat Ali; Naeem Iqbal; Farhat Abbas; Muhammad Sajid Aqeel Ahmad (Environmental Science and Pollution Research, 2014)

Effect of heavy metal pollution on mineral absorption in sunflower (Helianthus annuus L.) hybrids - Unaiza Aslam; Iftikhar Ahmad; Mumtaz Hussain; Ameer Khan; Abdul Ghani; Irfan Mustafa; Sabahat Jalal; Muhammad Anjum Aqeel; Saira Asif; Haroon Ahmed (Acta Physiologiae Plantarum, 2014)

Definitions and engineering classifications of tropical lowland peats - Mohamad Tarmizi Mohamad Zulkifley; Tham Fatt Ng; John Kuna Raj; Roslan Hashim; Azman Ghani; Mustaffa Kamal Shuib; Muhammad Aqeel Ashraf (Bulletin of Engineering Geology and the Environment, 2013)

Study of contaminant transport at an open-tipping waste disposal site - Muhammad Aqeel Ashraf; Ismail Yusoff; Mohamad Yusof; Yatimah Alias (Environmental Science and Pollution Research, 2013)

Monitoring trace elements generated by automobiles: air pollutants with possible health impacts - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2013)

Characterization of tannery effluent wastewater by proton-induced X-ray emission (PIXE) analysis to investigate their role in water pollution - Lubna Shakir; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2012)

Lead (Pb)-Induced Regulation of Growth, Photosynthesis, and Mineral Nutrition in Maize (Zea mays L.) Plants at Early Growth Stages - Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Qaisra Tabassam; Mumtaz Hussain; Humaira Firdous (Biological Trace Element Research, 2011)

Toxic Effect of Nickel (Ni) on Growth and Metabolism in Germinating Seeds of Sunflower (Helianthus annuus L.) - Muhammad Yasin Ashraf; Rumana Sadiq; Mumtaz Hussain; Muhammad Ashraf; M. Sajid Aqeel Ahmad (Biological Trace Element Research, 2011)